1994
DOI: 10.1113/expphysiol.1994.sp003803
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐base transport systems in a polarized human intestinal cell monolayer: Caco‐2

Abstract: SUMMARYAcid-base transport systems have been incompletely characterized in intact intestinal epithelial cells. We therefore studied the human cell line Caco-2, cultured on Teflon membranes to form confluent monolayers with apical microvilli on transmission electron microscopy and progressive enrichment in microvillar hydrolases. Monolayers (16-to 25-day-old), loaded with the pH-sensitive dye BCECF-AM (2',7'-bis (carboxyethyl)-5-carboxyfluorescein), were mounted in a spectrofluorometer cuvette to allow selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Acidification was followed by partial recovery in HEK293 cells ( Figure 5 ), as well as in CHO and Caco-2 cells (data not shown), as a result of pHi-regulatory mechanisms. [18][19][20] As a control, the injection of buffer containing 30 mM NaCl, instead of 30 mM propionate Na + , had no effect on pHi. …”
Section: Calibration Of Cmfda In Situmentioning
confidence: 99%
“…Acidification was followed by partial recovery in HEK293 cells ( Figure 5 ), as well as in CHO and Caco-2 cells (data not shown), as a result of pHi-regulatory mechanisms. [18][19][20] As a control, the injection of buffer containing 30 mM NaCl, instead of 30 mM propionate Na + , had no effect on pHi. …”
Section: Calibration Of Cmfda In Situmentioning
confidence: 99%
“…The observed difference between T84 and Caco-2 cells in their I SC responses to different concentrations of TMP suggested that colonic Cl -and HCO 3 -mediated secretions might be differentially elicited by the same agent depending on the concentrations used, probably due to differential expression of receptors, cotranspoters, exchangers and ion channels [10][11][12][13] leading to differential responses to TMP. This notion is supported by the observation that TMP at different concentrations could elicit different I SC responses from freshly isolated rat colon mucosa with distinct current characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…T84 cell line is a well-characterized colonic epithelial model that maintains a secretory phenotype similar to crypt base cells, and has been widely used to examine the regulation of intestinal Cl -secretion since CFTR and Na + -K + -Cl -cotransporter (NKCC) are highly expressed in this cell line [1,10,11] . The properties of human colonic Caco-2 cells are mostly close to those of mature absorptive villus/surface cells but they possess a certain CFTR characteristic of secretory cells [1,12,13] . However, few studies have been conducted to compare the secretory properties of these cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…This differential localization reflects the major roles (pHi homeostasis and transcellular Na+ absorption) of the two transporters. Studies using the human intestinal epithelial cell line Caco-2, however, provide conflicting evidence for NHE3 expression at the apical surface (Watson et al 1991 ;Osypiw et al 1994). In this study we have determined the expression of NHE isoforms in Caco-2 cells using a combination of molecular and cellular biological techniques (RT-PCR, 22Na+ influx and measurement of intracellular pH).…”
Section: Ne24hhmentioning
confidence: 99%